THE MANAGEMENT OF TEACHING ENGLISH WRITING AT KINDERGARTEN - Sulistiyani .; Norma Diana Fitri (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2020)
School-Based teaching English writing at kindergarten activities will improve student achievement, for example students who were once quiet now are active in the learning process. With the ongoing writting narrative text to form the potential for student learning, includes cognitive, affective and psychomotor aspects, student intelligent can be developed optimally hence it is well formed. With a constructivism approach, the teacher carries out learning in study groups. Students at kindergarten are divided into groups with heterogeneous members. In this study, researchers The researcher uses descriptive qualitative because it is more interested in the quality of a particular activity and then it will be evaluated and also it was designed to explain or to describe a condition objectively. This implies that the level of teaching English writing at kindergarten shows a positive impact. The level of of teaching English writing at kindergarten will give more influence well to the performance of teachers